Miswak’s Extract for Oral Care Reduces VAP Risk in Ventilated Patients: A Case Study - Fariz Jauhar Muslim; Arifin Dwi Atmaja (The Indonesian Institute of Science and Technology Research, 2026)
Ventilator-Associated Pneumonia (VAP) is a common nosocomial infection among patients receiving mechanical ventilation and is associated with increased morbidity, mortality, and prolonged length of stay in the intensive care unit (ICU). Poor oral hygiene is a key contributor to oropharyngeal bacterial colonization, which may facilitate the development of VAP. Miswak (Salvadora persica L.) contains natural antibacterial compounds and has potential as an alternative oral care intervention in nursing practice. This study employed an Evidence-Based Practice case study approach involving a mechanically ventilated patient in the ICU. Oral care using miswak extract was implemented for three consecutive days according to the established nursing care plan. Oral health status was assessed using the Beck Oral Assessment Score (BOAS), while the risk of VAP was evaluated using the Clinical Pulmonary Infection Score (CPIS). Following the intervention, oral hygiene improved significantly, as indicated by a reduction in the BOAS score from 7 to 3. The risk of VAP also decreased, demonstrated by a decline in the CPIS score from 7 (high risk) to 3 (low risk), accompanied by reduced purulent secretions and stable clinical parameters. These findings suggest that oral care using miswak extract is effective in improving oral hygiene and reducing VAP risk and may be recommended as a safe, practical, and evidence-based preventive intervention in ICU nursing practice.